Kajian kualitas perairan Teluk Gorontalo dengan menggunakan metode STORET - Miftahul Khair Kadim; Nuralim Pasisingi; Afriani R. Paramata (Depik Jurnal, 2017)
Good water quality is extremely important to support life of organisms. The determination of water quality status was needed as reference to monitor water pollution in aquatic system. This study aimed to assess the status of water quality in the Gorontalo Bay. There ware five sampling sites which represented the coastal condition and ecological characteristic. Sampling was carried out in May-July 2017. Sampling procedure of water samples carried out based on APHA standard method. Existing water quality data was analyzed by using STORET method. The result showed that Gorontalo bay obtained total score -39. It means the status of water quality the Gorontalo bay during sampling period in bad category.